If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -8) = 39 Reorder the terms: 4(-8 + 3x) = 39 (-8 * 4 + 3x * 4) = 39 (-32 + 12x) = 39 Solving -32 + 12x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 12x = 39 + 32 Combine like terms: -32 + 32 = 0 0 + 12x = 39 + 32 12x = 39 + 32 Combine like terms: 39 + 32 = 71 12x = 71 Divide each side by '12'. x = 5.916666667 Simplifying x = 5.916666667
| 33+c=54 | | 0.09a=9 | | 28+b=50 | | 12m-2m=90 | | 31-x=16 | | 0.1m=5 | | m+33=20 | | A+12=25 | | 0.02f=48 | | -4(3p+2)-45=5(2p+7) | | 2x^2-13x-19=0 | | 4/-6=-2 | | 21s=42 | | 3(x)+2(y)=45 | | -40+3y+4=2(3y-3)-9 | | ln(x+1)+ln(x+1)=4 | | 0.4b=390 | | 3(r-3)-1=2r+9 | | 7x+x=33 | | g(3)=3.2(3)+2.8 | | 49=7k | | 7(c-3)+9=6-c-18 | | 7x+149=5x+125 | | 49=ik | | 9n+n=2n-8 | | 93=31h | | 4b+5b=81 | | 17y=102 | | 8f+6=22 | | 9g=45 | | x-(-4)=x+9 | | 9x+210=7x+176 |